1999
DOI: 10.1002/(sici)1097-4644(19990401)73:1<137::aid-jcb15>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estradiol on aldosterone secretion in ovariectomized rats

Abstract: The effects and action mechanisms of estradiol on aldosterone secretion in female rats were studied. Replacement of estradiol benzoate (EB) increased the levels of plasma estradiol and aldosterone in ovariectomized (Ovx) rats. The aldosterone release from zona glomerulosa (ZG) cells was higher in EB-treated rats than in oil-treated animals. EB treatment potentiated the responses of aldosterone release to adrenocorticotropic hormone (ACTH), forskolin (FSK), and 8-bromoadenosine 3',5'-cyclic monophosphate (8-Br-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…However, these findings are in contrast to published studies on animal models, where progesterone increased aldosterone production by ASWT [17] and increased mRNA CYP11B2 production [17]. In our system, estradiol showed no effect on both ASCE and ASWT activities in contrast to the results reported by Kau, where an increase in the production of aldosterone by estradiol replacement in ovariectomised rat was shown [43]. …”
Section: Discussioncontrasting
confidence: 99%
“…However, these findings are in contrast to published studies on animal models, where progesterone increased aldosterone production by ASWT [17] and increased mRNA CYP11B2 production [17]. In our system, estradiol showed no effect on both ASCE and ASWT activities in contrast to the results reported by Kau, where an increase in the production of aldosterone by estradiol replacement in ovariectomised rat was shown [43]. …”
Section: Discussioncontrasting
confidence: 99%
“…However, in this study, both pregnant and nonpregnant women were in 100 mEq sodium balance. Nonetheless, other factors that are elevated in pregnancy may increase aldosterone synthase activity, such as estradiol (34).…”
Section: Discussionmentioning
confidence: 99%
“…Nowak et al (1995) indicated the stimulatory effect of oestradiol on basal corticosterone release in rats in vitro. Priming of ovariectomised rats with oestradiol benzoate causes an increase of basal and ACTHstimulated corticosterone (Lo et al, 2000) and aldosterone (Kau et al, 1999) release in vitro. On the other hand, Mesiano et al (1999) reported that oestradiol suppressed cAMP-induced cortisol secretion by H295 cells, whilst both basal and stimulated production of DHEA was enhanced.…”
Section: Discussionmentioning
confidence: 96%